Altimetry comparison, backward wave refraction and extreme wave analysis of NCEP data: Cape Point to Richards Bay - Barnes, Jarryd (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.